Optimasi Strategi Content Marketing sebagai Upaya Meningkatkan Customer Engagement pada Akun Sablon Shift - Diana Nofitasari; Rino Sardanto (Universitas Nusantara PGRI Kediri, 2023)
Screen Printing Shift is a service business that was founded in 2016. The purpose of this research is to find out how the Screen Printing Shift content marketing strategy works to increase customer engagement. This research method is qualitative with a case study approach. Data was collected through interviews with two people from Sablon Shift and two people from customers. The results of this method are expected to increase customer engagement. The process of increasing customer engagement is carried out by analyzing the content marketing strategy carried out by Sablon Shift by understanding several important points from the content marketing strategy, namely regarding design, current events, the reading experience, timing, and tone. With these points it is hoped that it can help increase customer engagement with Screen Printing Shift which can affect the number of sales.